The impact of increasing government domestic debt on the development of the capital market in Jamaica 1980-1995 - Morais, Chevanese ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Examines the growth in domestice debt since 1980. Discusses the economic rationale for the increased supply of government instruments on financial markets. Analyzes financial market developments given the increasing domestic debt over the past fifteen years.